Analisa Tingkat Kecelakaan pada Ruas Jalan Pangeran Antasari Kota Samarinda - Giusti, Anelda Anindita; EA, Benny Mochtar; Sundari, Yayuk Sri (Kurva S : Jurnal Keilmuan dan Aplikasi Teknik Sipil, 2023)
Handling traffic accidents on Jl. Pangeran Antasari Samarinda City is inadequate. To determine the level of traffic accidents on Jalan Pangeran Antasari, Samarinda City, we refer to traffic accident data originating from the Samarinda City Police Traffic Unit, while to determine the condition of the road section it is obtained by survey and direct observation at the research location. In this study, the Accident Rate (AR) data analysis method was used to determine the accident rate, the Equivalent Accident Number (EAN) to obtain Accident Prone Areas (Blackspot) and the Upper Control Limit Method (BKA). From the results of this research, it was found that the highest accident rate occurred in In 2021, the number of accidents was 10 incidents. This road section is included in an accident-prone area with a percentage of 94% and an Upper Control Limit value of 23 in 2020. Human awareness of safety when driving is very low, therefore, increase concentration and caution when driving.